Efficacy and safety of inclisiran in patients with cerebrovascular disease: ORION-9, ORION-10, and ORION-11 - Wolfgang Koenig; Kausik K. Ray; Ulf Landmesser; Lawrence A. Leiter; Gregory G. Schwartz; R. Scott Wright; Lorena Garcia Conde; Jackie Han; Frederick J. Raal (Elsevier, 2023)
Patients with cerebrovascular disease (CeVD) have been shown to benefit from lipid-lowering therapies, but guideline-recommended levels of low-density lipoprotein cholesterol (LDL-C) are often not attained with statin treatment alone. The ORION-9, ORION-10, and ORION-11 trials evaluated the efficacy and safety of inclisiran in 3660 primary and secondary prevention patients with hyperlipidemia despite maximum tolerated statin treatment. This pooled post hoc analysis comprised 202 randomized patients from those trials with established CeVD who had received either 284 mg inclisiran (equivalent to 300 mg inclisiran sodium, n = 110) or placebo (n = 92) on Days 1, 90, and 6-monthly thereafter up to Day 540. At baseline, mean (SD) LDL-C was 108.4 (34.3) mg/dL and 110.5 (35.3) mg/dL in inclisiran and placebo arms, respectively. Inclisiran produced a mean (95% CI) placebo-corrected percentage change in LDL-C from baseline to Day 510 of -55.2 (-64.5 to -45.9; p < 0.0001); the corresponding time-adjusted percentage change from baseline after Day 90 and up to Day 540 was -55.2 (-62.4 to -47.9; p < 0.0001). Treatment-emergent adverse events (TEAEs) and TEAEs at the injection site, mostly mild, were more frequent with inclisiran versus placebo (82.7% vs 70.7% and 3.6% vs 0%, respectively). In patients with CeVD, twice-yearly dosing with inclisiran (after the initial and 3-month doses) in combination with maximally tolerated statins provided effective and consistent LDL-C reductions and was well tolerated.